Análise do programa de residência pedagógica a partir da pedagogia histórico-crítica - Godim, Fernanda de Souza (2021)
The present study aims to analyze the Pedagogical Residency Program (PRP), intended for the initial teacher training of licensure courses, starting from the identification of its foundations and the pedagogical theories that guide its formation. Understanding the need to think about the formative process of the working class through a pedagogical theory that emancipates, Historical-Critical Pedagogy is adopted as a basis for the analysis to be carried out, contributing with a critical and investigative approach. It is a counter-hegemonic theory, which provides a broad understanding of the world and human formation and that, given the interests that surround the educational scope, goes beyond appearances. Therefore, this research is guided by the following questions that guide the investigation: which pedagogical theories influence the foundations of PRP? How do these theories differ from the presuppositions of teacher training defended by Historical-Critical Pedagogy? What are the political and ideological interests that permeate teacher training via PRP? Thus, the methodology adopted is based on the techniques of bibliographic study and document analysis. That said, it was possible to verify that the theories that underlie the PRP were influenced by the ideological current of neoliberalism and by the Global Movement for Education Reform, present in Brazil more intensely from the 1990s onwards, driven by the eagerness to form a subject adaptable to the market. It should be noted that the PRP is based on the Pedagogy of Competencies and on the Theory of the Reflective Teacher, given that both prioritize practice for the sake of practice. In view of this, it is observed that there is an attempt to replace theoretical training with a teacher training program that focuses on training teachers to apply a standardized curriculum based on Pedagogy of Competencies, valuing, to a large extent, everyday practice. From this perspective, the theory ends up being emptied, with this the initial training and the work of the future teacher become depoliticized and precarious. Therefore, it is necessary to understand the reality so that we are aware of all neoliberal rationality in the current context.